2021
DOI: 10.3390/cancers13153800
|View full text |Cite
|
Sign up to set email alerts
|

Post-Vaccination Anti-SARS-CoV-2-Antibody Response in Patients with Multiple Myeloma Correlates with Low CD19+ B-Lymphocyte Count and Anti-CD38 Treatment

Abstract: Few data are available regarding the efficacy of anti-SARS-CoV-2 vaccines in patients with hematological malignancies, and particular, plasma cell neoplasia. This ongoing single-center study aimed to describe the level of post-vaccination anti-SARS-CoV-2-antibodies depending on B lymphocyte count, current therapy, and remission status of patients with multiple myeloma and related plasma cell dyscrasia, after the first dose of anti-SARS-CoV-2 vaccination. The 82 patients included in this study received SARS-CoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(32 citation statements)
references
References 25 publications
(30 reference statements)
1
27
2
1
Order By: Relevance
“…Of the included 35 studies, 20 reported the seroconversion rate in cancer patients after partial COVID-19 immunization (2574 patients)[ 17 , 20 , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , 37 , [42] , [43] , [44] , [47] , [48] , [49] , [50] , [51] , [52] ] and 24 after complete vaccination schemes (4708 patients). [ [17] , [18] , [19] , [20] , 27 , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , 45 , 46 , 48 , 49 , 53 , 54 ] A lower seroconversion rate was achieved by those with incomplete vaccination regimens (51%; 95%CI 41-62) compared to those with fully immunized patients (73%; 95%CI 64-81) ( P =0.0009) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of the included 35 studies, 20 reported the seroconversion rate in cancer patients after partial COVID-19 immunization (2574 patients)[ 17 , 20 , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , 37 , [42] , [43] , [44] , [47] , [48] , [49] , [50] , [51] , [52] ] and 24 after complete vaccination schemes (4708 patients). [ [17] , [18] , [19] , [20] , 27 , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , 45 , 46 , 48 , 49 , 53 , 54 ] A lower seroconversion rate was achieved by those with incomplete vaccination regimens (51%; 95%CI 41-62) compared to those with fully immunized patients (73%; 95%CI 64-81) ( P =0.0009) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In a pooled analysis of 14 studies including patients with hematologic or solid malignancies,[ 17 , 20 , 24 , [28] , [29] , [30] , [31] , 33 , 34 , 37 , 42 , 47 , 49 , 52 ] a subsequent SARS-CoV-2 infection was documented in 0.78% (95%CI 0.18-3.26; I 2 = 33%) of the 1444 patients with a partial COVID-19 vaccination regimen and in 0.41% (95%CI 0.09-1.89; I 2 = 51.5%) of the 3000 patients with a complete vaccination regimen ( P= 0.4976 ) . Overall, patients with cancer had a 0.55% (95%CI 0.20-1.5; I 2 = 59.5%) likelihood of SARS-CoV-2 infection after being immunized with at least 1 dose of COVID-19 vaccines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected 18 series that provided anti-SARS-CoV-2 spike protein IgG seroconversion rates after full COVID-19 vaccination detailed by hematologic malignancy diagnosis, with at least 20 patients per group (Figure 1 and Supplemental Table 1) (2,(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The literature review also included six additional series that are not included in Figure 1, three due to sampling of serum antibodies before achieving full vaccination as evidenced by lower seroconversions in the healthy control group compared to the rest of the series (20,21), and three that did not provide breakdown of the data according to different histological diagnoses (22,23). There are a lot of variables that were not uniform in these series.…”
Section: Main Textmentioning
confidence: 99%
“…This prospective observational study included patients who met all of the following criteria: Furthermore, healthcare workers of the same sex and vaccination regime were selected as a healthy comparison group and included in the current analysis [26]. This single-center analysis was performed between January 1st and July 30th 2021 at the department of oncology and hematology of the University Medical Center Hamburg-Eppendorf, Germany, and included partially the same patient cohort as in our previously reported analysis [23]. Exclusion criteria were a prior confirmed infection with SARS-CoV-2, defined as either a polymerase-chain-reaction-test-validated infection or evidence of anti-SARS-CoV-2 nucleocapsid and spike protein antibodies before immunizations.…”
Section: Study Design and Patientsmentioning
confidence: 99%